Whole-body nitrogen utilization and tissue protein and casein synthesis in lactating primiparous sows fed low- and high-protein diets. (2nd June 2018) - Huber, Lee-Anne; Rudar, Marko; Trottier, Nathalie L; Cant, John P; de Lange, Cornelis F M
Abstract: Twenty-eight lactating Yorkshire and Yorkshire × Landrace primiparous sows were used to test the hypothesis that feeding a diet with reduced CP concentration and supplemented with crystalline AA (CAA) does not decrease milk protein yield and litter growth but improves apparent N utilization for milk protein production. Sows were assigned to 1 of 2 dietary treatments: 1) control (CON; 16.2% CP; analyzed content) or 2) low CP with CAA to meet estimated requirements of limiting AA (LCP; 12.7% CP) over a 17-d lactation period. A N balance was conducted for each sow between days 13 and 17 of lactation. On day 17, a 12-h primed continuous infusion of l -[ring- 2 H5 ]-Phe was conducted on 12 sows ( n = 6) with serial blood and milk sampling to determine plasma AA concentrations and Phe enrichment, and milk casein synthesis, respectively. Thereafter, sows were sacrificed and tissues were collected to determine tissue protein fractional synthesis rates (FSR). Litter growth rate and milk composition did not differ. Sows fed the LCP diet had reduced N intake (122.7 vs. 153.2 g/d; P < 0.001) and maternal N retention (13.5 vs. 24.6 g/d; P < 0.05) and greater apparent efficiency of using dietary N intake for milk production (85.1% vs. 67.5%; P < 0.001). On day 17 of lactation, all plasma essential AA concentrations exhibited a quartic relationship over time relative to consumption of a meal, where peaks occurred at approximately 1- and 4-h postprandial ( P < 0.05). Protein FSR in liver, LM, gastrocnemius muscle, mammary gland, and in milk caseins did not differ between treatments. Feeding primiparous sows with a diet containing 12.7% CP and supplemented with CAA to meet the limiting AA requirements did not reduce milk protein yield or piglet growth rate and increased the apparent utilization of dietary N, Arg, Leu, Phe+Tyr, and Trp for milk protein production. The improved apparent utilization of N and AA appears to be related exclusively to a reduction in N and AA intake.